Comparative study between public higher education systems from the regional approach of mobility and accreditation: Ecuador - Argentina - Muniz Cueva, Angela (Revista Universidad de Guayaquil, 2021)
In this article, the public politics that are included into the university educational system were analyzed with a particular approach in mobility and accreditation of the educational community in Ecuador and Argentina. In the last twenty years the public university educational system has bee having consistencies and inconsistencies, this was a hindrance for the country, because it can’t keep academic bilateral agreements with Argentina. On the other hand, Argentina is a referee into the public university educational system because it has an ample academic contribution through literary and scientific production, so this country is very attractive to the educational community in Latin American.